Analysis challenges and solutions in developing accounting resources for vocational schools - Salwa Salsabila; Elva Hanov Rais Satianingsih; Khansa Aulia Syahidah; Angga Hadiapurwa (Universitas Pendidikan Indonesia, 2025)
Good learning tools will optimally support the implementation of the curriculum to improve education quality and student learning outcomes. Vocational education has an important role in preparing students to enter the workforce, with accounting as one of the key competencies that requires relevant and up-to-date learning tools. However, there are significant challenges in the preparation of learning tools, including the lack of alignment between the curriculum and industry needs and limited resources that result in students feeling less connected to the teaching materials. This study aims to describe the problems and solutions in developing accounting learning tools in vocational schools and their impact on the effectiveness of the student learning process. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques used interviews and observations. The results showed several problems in preparing learning tools, including the lack of training for teachers, which makes it difficult for teachers to adjust, and the lack of supporting infrastructure. Solutions that can be done are developing technology-based learning tools, conducting regular training, discussions, and evaluations. Abstrak Perangkat pembelajaran yang baik akan mendukung pelaksanaan kurikulum secara optimal untuk mendukung peningkatan kualitas pendidikan dan capaian pembelajaran peserta didik. Pendidikan kejuruan memiliki peran penting dalam mempersiapkan peserta didik memasuki dunia kerja, dengan akuntansi sebagai salah satu kompetensi utama yang membutuhkan perangkat pembelajaran yang relevan dan mutakhir. Namun, terdapat tantangan besar dalam penyusunan perangkat pembelajaran, termasuk kurangnya keselarasan antara kurikulum dan kebutuhan industri, serta keterbatasan sumber daya yang mengakibatkan peserta didik merasa kurang terhubung dengan materi ajar. Penelitian ini bertujuan mendeskripsikan permasalahan dan solusi dalam menyusun perangkat pembelajaran akuntansi di SMK serta dampaknya pada efektivitas proses belajar peserta didik. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan wawancara dan observasi. Hasil penelitian menunjukkan bahwa ada beberapa permasalahan dalam menyusun perangkat pembelajaran diantaranya kurangnya pelatihan bagi guru sehingga guru sulit menyesuaikan dan kurangnya sarana prasarana yang mendukung. Solusi yang dapat dilakukan mengembangkan perangkat pembelajaran berbasis teknologi, melakukan pelatihan, diskusi, dan evaluasi secara berkala. Kata Kunci: pengembangan kurikulum; perangkat pembelajaran; proses belajar peserta didik